Epigallocatechin-3-gallate PEGylated poly(lactic-co-glycolic) acid nanoparticles mitigate striatal pathology and motor deficits in 3-nitropropionic acid intoxicated mice - Cano, Amanda (2020)
Aim: To compare free and nanoparticle (NP)-encapsulated epigallocatechin-3-gallate (EGCG) for the treatment of Huntingtons disease (HD)-like symptoms in mice. Materials & methods: EGCG was incorporated into PEGylated poly(lactic-co-glycolic) acid NPs with ascorbic acid (AA). HD-like striatal lesions and motor deficit were induced in mice by 3-nitropropionic acid-intoxication. EGCG and EGCG/AA NPs were co-administered and behavioral motor assessments and striatal histology performed after 5 days. Results: EGCG/AA NPs were significantly more effective than free EGCG in reducing motor disturbances and depression-like behavior associated with 3-nitropropionic acid toxicity. EGCG/AA NPs treatment also mitigated neuroinflammation and prevented neuronal loss. Conclusion: NP encapsulation enhances therapeutic robustness of EGCG in this model of HD symptomatology. Together with our previous findings, this highlights the potential of EGCG/AA NPs in the symptomatic treatment of neurodegenerative diseases.